A Case Study of a Turnaround High School: An Examination of the Maryland State Department of Education Breakthrough Center Intervention. Issue 4 (1st October 2016) - Galindo, Claudia; Stein, Kathleen; Schaffer, Eugene
ABSTRACT: This study examined the Maryland State Department of Education Breakthrough Center (BTC) engagement in a Baltimore City turnaround high school. Utilizing a case-study design and mixed-methods research, data were collected through interviews, informal observations, and review of administrative and achievement documents. Beginning in the 2011–2012 academic year, the BTC has been working in collaboration with school personnel to improve the educational experiences and academic achievement of students. School personnel recognized that the BTC has been responsive to teachers' requests and has exhibited a flexible approach building collaborative and nonevaluative relations. Administrative and achievement data also indicated improvement in school outcome measures during the past 3 years. Nevertheless, school faculty also identified important challenges of the BTC intervention, such as the relevance of this intervention for veteran teachers, the extent to which the needs of all student populations were met, and the sustainability of the intervention.